Ação educativa e percepções de agricultores: importância das abelhas e impactos causados pelo uso de agrotóxicos - ZEFERINO, Edileno Schmidt (2019)
The objective of this article is to understand the perceptions and the knowledge about the importance of the bees and the relation with the use of the agrotoxic of familiar farmers, with the objective of understanding the farmers' perceptions and knowledge about the bees and the relation with the use of the pesticides to orient proposition of educational actions in the Nossa Senhora Aparecida Community of São Francisco de Assis, in the municipality of Brasil Novo, Pará. Semistructured interviews were carried out, through which an action plan was developed to be developed with the students of the 7th year, according to the matrix of skills and abilities of the curriculum adopted in Brasil Novo, Pará, in expository and field classes. The lesson sought to demonstrate how important bees are to the ecological balance, through pollination of plants, which also benefits the world economy, national and regional, through agricultural production.